Associations between triglyceride-glucose index and different hypertension subtypes: A population-based study in China - Cai, Qian; Xing, Cathleen Y.; Zhu, Jiang; Wang, Ying; Lu, Fanghong; Peng, Jie (Frontiers in Cardiovascular Medicine, 2022)
Background: Abnormal glycolipid metabolism plays a crucial role in hypertension. While an elevated triglyceride-glucose (TyG) index has been recognized as a risk factor of developing hypertension, the associations of TyG index and different hypertension subtypes, namely isolated systolic hypertension (ISH), isolated diastolic hypertension (IDH), and systolic-diastolic hypertension (SDH) remain unclear. This study was designed to investigate the associations of TyG index and hypertension subtypes in a general Chinese population. Methods: In a sample of 16,793 participants from Shandong Province, China, multivariate logistic regression analyses were performed to examine the associations between TyG index and different hypertension subtypes. Loess smooth curves were fitted to visualize the trends. Stratified analyses were conducted to further assess the potential interactions in the associations of TyG index and different hypertension subtypes. Results: A higher TyG index was associated with an increased odds of having IDH (OR=2.94, 95% CI: 1.66, 5.23) and SDH (OR=1.82, 95% CI: 1.33, 2.49), whereas no apparent relationship was observed between TyG index and ISH. With respect to sex, the effect of TyG index on having IDH and SDH was significant in women, but not in men. Participants with lower lipid profiles and glucose levels demonstrated a stronger strength of association between TyG index and IDH as compared to the TyG index-SDH association. Stratified analysis showed that participants with a higher TyG index were more than 3 times more likely to have IDH and SDH among persons 18-42 years of age. Significant interactions were observed between TyG index and sex, age, and high-density lipoprotein cholesterol (HDL-C) in the SDH group, and a significant interaction was also found between TyG index and body mass index (BMI) in the ISH group. Conclusions: TyG index may potentially serve as a novel indicator for IDH and SDH. Our findings could also inform the development and implementation of targeted screening for hypertension.